Incidental finding of giant pericardial lipoma. (21st November 2016) - Salim, Handi; Anand, Dhakshinamurthy Vijay; Watkin, Richard; Tapp, Luke
Abstract : We describe a patient with an incidental finding of a large mass adjacent to the heart detected on a screening CT scan. The differential diagnosis included primary and secondary tumours of the heart. Subsequent investigation with trans-thoracic echocardiogram and cardiac MRI confirmed a diagnosis of a giant pericardial lipoma, one of the common benign primary cardiac tumours.